After the Ax Falls: Job Loss as a Career Transition - Latack, Janina C.; Dozier, Janelle Brinker (Academy of Management Review, 1986)
Despite the improving economy, consolidation and staff reductions characterize the human resource staffing policies of many firms. Furthermore, economic and demographic pressures indicate that involuntary job loss will be an increasingly common experience for managers and professionals in the coming decade. Based on a synthesis of empirical studies, this paper proposes a model showing factors which may generate career growth from job loss. Organizational strategies are recommended for creative management of this career transition and suggestions are provided to focus future research.